Von-Willebrand Disease Presenting as Intractable Epistaxis after Nasal Polypectomy - Jeong Jin Park; Chang-Hoon Kim; Jeung-Gweon Lee; Hyung-Ju Cho (Case Reports in Otolaryngology)
Von-Willebrand disease (VWD) is one of the platelet dysfunction disorders that results from a deficiency of Von-Willebrand factor, which is essential for hemostasis. VWD patients typically have normal laboratory results on screening for bleeding disorders. To suspect and diagnose VWD, a careful review of past medical history and laboratory tests is critical. A 59-year-old male patient presented with intractable nasal bleeding after nasal polypectomy. The bleeding was controlled by platelet transfusion, and he was later diagnosed with VWD.